انتقاد المعاصرين لأحاديث الصحيحين الخاصة بالأماكن والبلدان - Yusuf, M. Y.; Rasheed, M. A. (Universiti Sains Islam Malaysia, 2024)
Al-Sahihayn are the major hadith compilations in which contains the sources of the law second only to the al-Quran al-Karim. In light of the high prominence rendered to them, it is not surprising that it is often the target for modern-day criticism as well as of the past whether in the form of scholarly criticism or point-blank slanderous. This study was conducted to discuss the modern scholarly criticism of selected hadiths in al-Sahihayn and to answer all the criticism that had been thrown. They made the hadith as a field of criticism as if to impose on the public that the hadith is contrary to the al-Quran, one that nullifies the infallibility of the Prophet (peace be upon him), one that which is unauthentic and devoid of credence. Data for this research is obtained through literary reviews before the same be subjected to analysis based on inductive and deductive methods. The findings of this study reveal contradictory evidence which proves the validity that hadiths and simultaneously answers and denies the criticism.